Do Innovativeness, Proactiveness, and Risk-Taking affect Business Performance? : Entrepreneurial insights of FAMAs Entrepreneurs - Nur Asyiqin Binti Abdul Manaf; Ku Halim bin Ku Ariffin; Muhammad Dharma Tuah Putra Nasution; Yossie Rossanty (International Journal of Business Economics (IJBE), 2021)
The study aimed to investigate the relationship between innovativeness, proactiveness, and risk-taking on the performance of FAMA's entrepreneurs in Malaysia. Following a comprehensive review, the study has proposed the dimensions that would correlate with the performance of FAMA's entrepreneurs include innovativeness, proactiveness, and risk-taking. This study was conducted via the gathering of primary data, and the questionnaire was sent to firms across Kedah state. Approximately 100 sets of questionnaires were distributed and the gathered data was transferred into statistical computing. The study's findings indicated that dimensions such as innovativeness and risk-taking have a strong correlation with the performance of FAMA's entrepreneurs. However, the proactiveness dimension does not have a correlation with business performance. The current study enables firms to investigate key factors that contribute to performance.